ANALYSIS OF INEFFECTIVENESS OF INDONESIAN SENTENCES IN STUDENTS' THESIS WRITING (A CASE STUDY OF SOCIOLOGY STUDENTS' THESES AT MUHAMMADIYAH UNIVERSITY OF MAKASSAR) - Asmabuasappe Asmabuasappe; Muhammad Darwis; Kaharuddin Kaharuddin (International Journal of Social Science, 2023)
The aim of this study is to describe the forms of sentence ineffectiveness in the theses of students from the Faculty of Education at Muhammadiyah University of Makassar. This research falls under the category of qualitative descriptive study. The data for this study are obtained from students' theses using the observation method through note-taking technique. The results of the research reveal five forms of sentence ineffectiveness, namely (1) lack of fluency, (2) inaccuracy, (3) lack of clarity, (4) inefficiency, and (5) lack of parallelism